2019
DOI: 10.3390/ijms20123107
|View full text |Cite
|
Sign up to set email alerts
|

MMP-12, Secreted by Pro-Inflammatory Macrophages, Targets Endoglin in Human Macrophages and Endothelial Cells

Abstract: Upon inflammation, monocyte-derived macrophages (MΦ) infiltrate blood vessels to regulate several processes involved in vascular pathophysiology. However, little is known about the mediators involved. Macrophage polarization is crucial for a fast and efficient initial response (GM-MΦ) and a good resolution (M-MΦ) of the inflammatory process. The functional activity of polarized MΦ is exerted mainly through their secretome, which can target other cell types, including endothelial cells. Endoglin (CD105) is a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 71 publications
0
47
0
Order By: Relevance
“…Cell-surface endoglin expression is also regulated via receptor shedding. Our previous work showed that the membrane-bound protease Matrix Metalloproteinase-14 (MMP-14, also known as Membrane Type-1 MMP) is able to cleave endoglin in the extracellular domain close to the cell membrane [25], and the same phenomenon was seen by Aristorena et al for MMP-12 secreted by inflammatory macrophages [26], which generated a soluble form of endoglin (sol-eng). Sol-eng can disturb vascular remodeling and maintenance, resulting in vascular abnormalities.…”
Section: Endoglin Structure and Functionmentioning
confidence: 57%
“…Cell-surface endoglin expression is also regulated via receptor shedding. Our previous work showed that the membrane-bound protease Matrix Metalloproteinase-14 (MMP-14, also known as Membrane Type-1 MMP) is able to cleave endoglin in the extracellular domain close to the cell membrane [25], and the same phenomenon was seen by Aristorena et al for MMP-12 secreted by inflammatory macrophages [26], which generated a soluble form of endoglin (sol-eng). Sol-eng can disturb vascular remodeling and maintenance, resulting in vascular abnormalities.…”
Section: Endoglin Structure and Functionmentioning
confidence: 57%
“…So now we consider not only the contribution of cancer cells but also that of the macrophages to the secretion of the various classes of matrix metalloproteinases (Aristorena et al. 2019 ; Huang et al. 2012 ).…”
Section: Multiscale Modelling Of Tumour and Dynamics Within Fibrous Ementioning
confidence: 99%
“…More detailed statistic data are provided in Supplementary Table 5 ◂ the F4/80 staining was again fainter. We then studied the mRNA expression of osteopontin (Spp1), which is a marker for reparative macrophages [49,55,57], the matrix metalloproteinase 12, a macrophage-specific elastase expressed in pro-inflammatory macrophages [4], and the lectin YM1 (CHI3L3), which is an indicator for reparative or alternatively activated macrophages [45]. Spp1 mRNA stayed elevated and continued to be significantly increased in 8 and 12 week-old Dsg2 MT mice (Fig.…”
Section: Distinct Macrophage Populations Accumulate and Differentiatementioning
confidence: 99%